A SPATIAL ANALYSIS OF MATERNAL HEALTH CARE IN PUNJAB, PAKISTAN - Asima Ihsan; Faizan Ali; Yasir Zada Khan; Shahid Adil (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The aim of this study is to analyze the barriers associated with maternal healthcare in Punjab (Pakistan) and to identify the factors contributing to maternal mortality. The study used the Multiple Indicator Cluster Survey (MICS-2018), data to analyze the socio-economic inequalities and determinants in the use of the maternal healthcare in Punjab. The analysis of concentration curve and concentration index showed an inequality in the utilization of the maternal health services among different socio-economic groups. The lowest wealth quintile is underutilizing the maternal health services as compared to the richest quintile. Furthermore, maternal health services are more pronounced amongst women living in the urban areas than those living in the rural areas. The occurrence of the maternal deaths is also higher in the lowest quintile. Therefore, it can be concluded that low utilization may contribute to higher maternal mortality. The logistic regression is also performed to analyze the determinants of the maternal mortality for potential household. According to the results, if the household head is literate, there will be a lower level of risk of maternal death. The odd ratios of household heads and a lower risk of mortality persisted over 1.0002 times. The unsafe drinking water is more associated with maternal deaths and increased the risk of maternal deaths by 1.142 times. An increase in income is more likely to enhance the chance of maternal survival by 1.16 times. So, by putting it as the main cause of death, it may be concluded that maternal deaths occur due to low-utilization of the maternal health services.